2015
DOI: 10.1016/j.numecd.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic index, glycemic load and glycemic response: An International Scientific Consensus Summit from the International Carbohydrate Quality Consortium (ICQC)

Abstract: Given the high prevalence of diabetes and pre-diabetes worldwide and the consistency of the scientific evidence reviewed, the expert panel confirmed an urgent need to communicate information on GI and GL to the general public and health professionals, through channels such as national dietary guidelines, food composition tables and food labels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
463
2
35

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 571 publications
(504 citation statements)
references
References 189 publications
4
463
2
35
Order By: Relevance
“…Finally, a recent consensus summit and review indicated that lower GI, GL and glycaemic response might also reduce the risk of acquiring several different cancers. 13,44 Consuming too many higher or high-GI starchy staples does not appear to be good for people in the general population, particularly so for obese, T2D and pre-diabetes patients. We consider this is linked to higher or rapid rates of glucose absorption and the consequential higher blood glucose levels after digestion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a recent consensus summit and review indicated that lower GI, GL and glycaemic response might also reduce the risk of acquiring several different cancers. 13,44 Consuming too many higher or high-GI starchy staples does not appear to be good for people in the general population, particularly so for obese, T2D and pre-diabetes patients. We consider this is linked to higher or rapid rates of glucose absorption and the consequential higher blood glucose levels after digestion.…”
Section: Discussionmentioning
confidence: 99%
“…of baked potato is shown to be equivalent to 22 g of pure glucose, which is important information, especially for someone with diabetes. The epidemiological work on incident T2D initiated by Salmeron et al 19,20 has now been expanded to 24 studies worldwide, for which meta-analyses reveal a strong dose-response T2D-GL relation, 21 implying with support of interventional studies 13 that diets lower in GL can be preventative of T2D. The GL per standard serving of food item also varies ( Figure 2).…”
Section: Glycaemic Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…Selama ini untuk pengendalian kadar glukosa darah pasien DM menggunakan pendekatan farmakologi, namun beberapa uji klinik menunjukkan bahwa kontrol diabetes dapat dilakukan dengan diet indeks glikemik rendah dari pada indeks glikemik tinggi (Augustin et al, 2015)Makanan dengan nilai IG tinggi menyebabkan respons glukosa darah dan insulin lebih tinggi dibandingkan dengan makanan yg nilai IG nya rendah. Konsumsi pangan IG tinggi lebih cepat diserap di dalam usus halus dan berpotensi terjadi peningkatan glukosa darah.…”
Section: Metode Penelitianunclassified
“…En este sentido, uno de los indicadores que permite clasificar a los alimentos según la calidad de los carbohidratos (CHO) midiendo su velocidad de absorción es el índice glicémico (IG); mientras que la carga glicé-mica (CG) es un término más reciente que relaciona la calidad y la cantidad de CHO por gramos de porción habitual de consumo. Ambos permiten reducir el impacto glucémico postprandial sin la restricción total de los carbohidratos en la dieta (10).…”
Section: Introductionunclassified